Development of equations and software for estimating weight in children with cerebral palsy - Ruiz Brunner, María de Las Mercedes (2021)
Aim: To develop equations and software to estimate weight using segmental measures for children with cerebral palsy (CP). Method: This was a cross-sectional study. Children and adolescents with CP of both sexes from 2 to 19 years old from five cities in Argentina were included. Weight, mid-upper arm circumference (MUAC), and clinical covariables were collected. Linear regression models with weight as the dependent variable and body segment lengths as predictors were developed and compared for R2, adjusted R2, and the root mean square of the error. Results: In total, 381 children and adolescents (mean age 10y 5mo [SD 4y 9mo], range 2–19y; 231 males, 150 females) with a confirmed diagnosis of CP were included. Gross motor function based on the Gross Motor Function Classification System (GMFCS) was as follows: level I, 59; II, 55; III, 59; IV, 69; V, 139. The interaction between weight and other variables such as MUAC, sex, GMFCS, and age was analysed. The concordance correlation coefficient between estimated and observed weight was 0.94 (95% CI 0.93–0.95). From the results of the equations, a free software tool, named Weight Calculator CP, was developed. Interpretation: Weight in children with CP can be predicted using MUAC, GMFCS, and age. Weight Calculator CP can be used in clinical practice when direct weight cannot be obtained. What this paper adds Equations can be used to estimate weight in children with cerebral palsy via body segments. Weight can be estimated according to age and gross motor function. The average difference between estimated and observed weights was 119g.